Phytochemical content and antioxidant capacity of ethyl acetate extracts from fifteen Orthosiphon aristatus leaves genotypes - RAISADIBA PUTRI BOVANI; NOVIAN LIWANDA; IRMANIDA BATUBARA; LAKSMI AMBARSARI; WARAS NURCHOLIS (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Bovani RP, Liwanda N, Batubara I, Ambarsari L, Nurcholis W. 2024. Phytochemical content and antioxidant capacity of ethyl acetate extracts from fifteen Orthosiphon aristatus leaves genotypes. Biodiversitas 25: 763-769. Orthosiphon aristatus (Blume) Miq., also known as kumis kucing in Indonesia, is a medicinal plant belonging to the Lamiaceae family that contains various phytochemical compounds with antioxidant properties. This study investigated the phenolic content, flavonoid, rosmarinic acid,  sinensetin,  and antioxidant capacity of 15 genotypes of O. aristatus ethyl acetate extracts. Therefore, 15 genotypes were analyzed using quercetin as the standard for Total Phenolic Content (TPC) using a colorimetric method with gallic acid and Total Flavonoid Content (TFC). Sinensentin and rosmarinic acid were measured by High-Performance Liquid Chromatography (HPLC). Antioxidant capacity was determined using Trolox as a standard antioxidant by 2-Diphenyl Picrylhydrazyl (DPPH) and Ferric Reducing Antioxidant Power (FRAP) assays. The results revealed a diverse range of phytochemical compounds, with total phenolic content ranging from 3.39 to 13.80 mg GAE/g DW, total flavonoid content from 0.20 to 1.43 mg QE/g DW, rosmarinic acid from 0.02 to 0.19 mg/g DW, and sinensetin from 1.61 to 21.67 mg/g DW. Furthermore, the antioxidant assays demonstrated varying degrees of efficacy, with DPPH ranging from 2.09 to 13.98 ?mol TE/g DW and FRAP from 0.07 to 2.96 ?mol TE/g DW. Genotypes A10, A11, and A12 exhibited superior phytochemical contents and antioxidant capacities, highlighting their potential as valuable sources of medicinal compounds.